Economic administration - Retrospect and prospect - Need for sustainable strategies - Lakshminarayanan, P. (2009)
After Independence, with the emphasis on planned development, it was the responsibility of the Government of India (economic administration) to do whatever possible to ensure that the targets laid down in the Plans were fulfilled. In the present context of economic crisis in the globalised era, the Government must adopt, keeping in view of the mantra "growth with equity", certain strategies for sustaining the development. It is recognised that promotion of self-employment as one of the best strategy for bringing individuals into the mainstream of society as a productive and contributing individual. Reproduced.
Keywords: Economic and social development